2010
DOI: 10.1080/00071660903419518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet, age and gender on the polyunsaturated fatty acid composition of broiler anatomical compartments

Abstract: 1. The objective of this study was to investigate the effect of dietary fatty acid (FA) composition, age, and gender on the FA composition of different broiler anatomical compartments. Four dietary fat sources (palm fat, P; soybean oil, S; linseed oil, L; fish oil, F) were added to a wheat-soybean meal based diet at 30 g/kg in addition to 50 g/kg palm fat. Diets were fed separately to female and male birds from d 1 to either d 21 or d 42 of age. 2. The total FA content (mg/100 g tissue) and the FA composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 27 publications
9
29
0
Order By: Relevance
“…These results are in line with Poureslami et al (2010) whose study of the effect of age on fatty acid metabolism revealed that chickens slaughtered at 42 days of age had higher values for PUFA intake, PUFA apparent digestibility and ALA and LCP derivates accumulation when compared with the 7-14 d age period, lied to lower values for boxidation. Authors justified this trend with the fact that young birds had a higher metabolism rate compared to the older ones.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These results are in line with Poureslami et al (2010) whose study of the effect of age on fatty acid metabolism revealed that chickens slaughtered at 42 days of age had higher values for PUFA intake, PUFA apparent digestibility and ALA and LCP derivates accumulation when compared with the 7-14 d age period, lied to lower values for boxidation. Authors justified this trend with the fact that young birds had a higher metabolism rate compared to the older ones.…”
Section: Resultssupporting
confidence: 78%
“…The final metabolite, DHA, is synthesised by chain elongation, D 6 -desaturation and peroxisomal b-oxidation of DPA (Poureslami et al, 2010).…”
mentioning
confidence: 99%
“…amount of total SFA compared to meat line quails (P<0.01), and particularly, a higher (P<0.01) proportions of lauric (C12:0; 2-fold higher), myristic (C14:0), palmitic (C16:0), heptadecanoic (C17:0) and stearic (C18:0) acids. The proportions of the single SFA found in the present study were consistent with those reported in literature on quails (Botsoglou et al, 2004;Genchev et al, 2008;Boni et al, 2010;Gecgel et al, 2015) and on chicken (Rule et al, 2002;Poureslami et al, 2010). The total monounsaturated fatty acids (MUFA) content, which in chickens is related either to the endogenous synthesis or to the gut absorption from the diet, was highest in meat-type quails (+ 11.5 p.p.…”
Section: Total Lipid Cholesterol Contents and Fatty Acid Compositionsupporting
confidence: 81%
“…This corresponds to the results of our study. Similarly, Poureslami et al (2010a) stated that the content of PUFA n3 and n6 in various parts of broiler chickens decreased with their age. On the other hand, Baeza et al (2000) found in duck meat that age did not have an effect on contents of SFA and MUFA up to 90 days of age.…”
Section: Resultsmentioning
confidence: 99%
“…Pheasant meat in particular, thanks to the high content of some proteins and the low content of fat that moreover shows a higher proportion of essential fatty acids (FA), is a highly valued food, outdoing even the nutritional value of broiler chicken meat (Straková et al 2006;Straková et al 2011;Vitula et al 2011). Poureslami et al (2010a) found that the effect of age on the proportions of FA in broiler chickens was only negligible. On the other hand, Poureslami et al (2010b) discovered an increase in elongase activity as broiler chickens aged.…”
mentioning
confidence: 99%